PENGARUH UANG YANG BEREDAR (M2), KURS, INFLASI DAN TINGKAT IMBALAN SBIS TERHADAP BETA SAHAM SYARIAH (JAKARTA ISLAMIC INDEX) DAN INDEKS HARGA SAHAM GABUNGAN (IHSG) - SE, M.Si, Ak, Murtini; SE, M.Si, Ak, Rini Hidayah; Barotuttaqiyah,SE, Mardela Nurul (STIE Muhammadiyah Pekalonga, 2015)
The purpose of this research is to know and to analyze the impact of revolving money (M2), exchange rate, inflation and SBIS returnÂ level on the beta of syariah stock and Jakarta composite index. The technique that is used to take samples is purposive sampling with criteria of companies that is constantly listed in JIC since 2009 â 2013. The analysis in this research is using secondary data that is classified in time series data and naturally quantitative. The analyzing tool that is used in this research is path analysis, which the analysis result is done after model filling the condition of normality test, outlier data, multiocolinierity and singularity. This research is using path analysis method, with using goodness fit test which is every single variable using 1% significance level. The result of the research shows that revolving money variable (M2), exchange rate andÂ inflation have significant impact on SBIS return level. Revolving money variable (M2) and SBIS return level donât have significant impact on beta of syariah stock (JII). Inflation variable and SBIS return level have significant impact on Jakarta composite index, while beta of syariah stock variable doesnât have significant impact on Jakarta composite index. Key words : Jakarta composite index, beta of syariah stock, SBIS return level, revolving money, exchange rate, inflation.